2016
DOI: 10.4236/ce.2016.78120
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Fluency Correlates with Students’ Ratings of Their Learning and Their Instructor in an Actual Course

Abstract: The experience of ease or fluency that occurs when learners acquire information is often highly related to their metacognitive judgments of learning for that information. Laboratory-based research indicates that fluency can contribute to students' overconfident judgments of learning and predictions of future test performance. Such research, however, typically involves artificial learning situations presented for brief periods of time and without a strong investment on the part of the learners. In actual course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…Consistent results have also been obtained in a classroom study (Serra & Magreehan, 2016). Undergraduate students in 25 introductory psychology courses at the same university were invited to complete an online questionnaire at the end of the semester.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent results have also been obtained in a classroom study (Serra & Magreehan, 2016). Undergraduate students in 25 introductory psychology courses at the same university were invited to complete an online questionnaire at the end of the semester.…”
Section: Introductionsupporting
confidence: 85%
“…Coats and Smidchens (1966) attributed students' high performance to learning from a highly expressive instructor, a dynamic lecturer, or an enthusiastic lecturer versus a static speaker who read from a manuscript. Serra and Magreehan (2016) also found a small, but significant correlation ( r = .13) between perceived lecturer fluency and learning performance. Similarly, Carpenter, Mickes, et al (2016) conducted a study very similar to the current research, and found a significant effect of fluency on actual learning performance in one of their three experiments (see Experiment 3).…”
Section: Discussionmentioning
confidence: 95%
“…The positive impression that students have of fluent, engaging, or enthusiastic instructors may be leveraged in other ways as well. Although classroom-based research shows that such factors do not improve students' course performance (Bettencourt, Gillett, Gall, & Hull, 1983;Serra & Magreehan, 2016;Williams & Ceci, 1997), these factors may have positive effects on students' impressions of teachers that might be farther-reaching than we knew. Serra and McNeely (2020) report new data from a classroom study showing that instructors who are rated as more fluent are not only rated by students as more effective teachers (after controlling for course grades), but also rated by students as more likely to secretly be Batman, or to be capable of choreographing Beyoncé's music videos.…”
Section: Leveraging Fluency For the Greater Goodmentioning
confidence: 81%
“…This result parallels the findings from Refs. [63][64][65] that found students are more confident after viewing more fluent lectures even though the enhanced fluency often does not lead to greater learning. When working with easier content the enhanced fluency is more diagnostic of learning, leading students to make more accurate judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Students also often implicitly use heuristic-based cues, such as familiarity and fluency, when engaged in metacognitive monitoring to make judgments about the progress of their learning. The fluency with which individuals process information is related to metacognitive judgments, with individuals making higher metacognitive judgments in memory tasks for easier to read words and images [61,62], in comprehension tasks for fluently presented lectures or easier to process text [63][64][65][66], or in knowledge tasks for questions with familiar terms [67], even when these cues are not diagnostic of learning. The fluency with which an item is retrieved from memory is also related to metacognitive judgments [68,69].…”
Section: Metacognitionmentioning
confidence: 99%